(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
Folil Mapudungun is a multidimensional method, based on a communicative approach, for teaching and learning Mapuche as a second language (L2). It was designed for adult learners in a context where Mapudungun is a “language specific to the territory”, a heritage language and a community language. It is also the result of twelve years of research aiming to formulate objectives, and produce and systematize contents. At present, the method is constituted by eight lessons, developed and published in a textbook. This paper presents the method content organization according to three axes: transverse organization (based on six functional and formal categories), longitudinal organization (based on discursive, cultural and methodological principles), and local organization (based on methodological principles as well). It is claimed that the use of these three axes allows us to overcome the methodology-content dichotomy, and to favor the development of the various communicative competences used in everyday life.